Risky sexual behavior and STI testing among teens experiencing homelessness. (August 2022) - Halverson, McKenna; Hatchimonji, Danielle R.; Treglia, Dan; Flatley, Claire A.; Herbers, Janette E.; Cutuli, J.J.
Highlights: Students experiencing homelessness are more likely to display risky sexual behavior. Student homelessness was associated with increased likelihood of STI/HIV testing. These links were not moderated by student sex or LGB identity. Asian students experiencing homelessness are at high risk for risky sexual behavior. Abstract: Teens who experience homelessness are more likely to engage in risky sexual behavior, though less is reliably known about sexually transmitted infection (STI) testing rates in this group. We tested for differences in sexual behaviors and STI/HIV testing based on student homelessness and intersecting factors using data from the 2019 Youth Risk Behavior Survey administered in 7 states and 3 school districts. Students who experienced homelessness were more likely to report risky sexual behavior. Race moderated this link, suggesting that Asian students who experienced homelessness were at greater risk. Homelessness was linked to a greater likelihood of having been tested for STIs/HIV among those who seemed to be in groups recommended for testing. Student sex and lesbian, gay, and bisexual (LGB) identity did not moderate associations between homelessness and risky sexual behavior or STI/HIV testing. The overall sample demonstrated low STI testing rates, indicating a continued need to improve testing rates for all youth at risk for STIs/HIV.